1999
DOI: 10.1007/s002109900033
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a contribution of store-operated Ca 2+ channels to NO-mediated endothelium-dependent relaxation of guinea-pig aorta in response to a Ca 2+ ionophore, A23187

Abstract: A23187 (6S-[6alpha,8beta,9beta,11alpha]-5-(methylamino) -2-[[3,9,11-trimethyl-8-[1-methyl-2-oxo-2-(1H-pyrrol-2-yl)ethyl]-1,7- dioxaspiro[5.5]undec-2-yl]methyl]-4-benzoxazolecarboxylic acid, calcimycin), an antibiotic Ca2+ ionophore, produces an endothelium-dependent vascular relaxation. In the present study, pharmacological features were functionally characterized of endothelium-dependent relaxant response of guinea-pig aorta to A23187, especially focusing on the possible Ca2+ source and Ca2+ mobilization mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
3
15
0
2
Order By: Relevance
“…However: (1) a number of authors show that fish vascular beds are dilated by NO, and thus, provide evidence for an endothelial NO system in this taxa (Mustafa et al, 1997;Nilsson and Söderström, 1997;Mustafa and Agnisola, 1998); (2) several studies (Fritsche et al, 2000;McNeill and Perry, 2006;Wang et al, 2007;Amelio et al, 2008) have identified eNOS immunoreactivity in various fish tissues, including the vascular endothelium, when using heterologous mammalian eNOS antibodies (Olson and Donald, 2009;Imbrogno et al, 2014); and (3) Andreakis et al (2011) suggest that a neuronal NOS (nNOS) isoform with an 'endotheliallike' consensus may cover some functional features typical of the eNOS isoform. As has previously been reported for mammals (Taniguchi et al, 1999;Oliveira et al, 2009), we showed that NO is involved in A23187-mediated vasodilation of isolated trout coronary arterioles (Fig. 4A), and that this effect was completely dependent on the presence of an intact endothelium.…”
Section: Vasoactivity Of Recombinant Il-1β and The Effect Of Temperaturesupporting
confidence: 87%
“…However: (1) a number of authors show that fish vascular beds are dilated by NO, and thus, provide evidence for an endothelial NO system in this taxa (Mustafa et al, 1997;Nilsson and Söderström, 1997;Mustafa and Agnisola, 1998); (2) several studies (Fritsche et al, 2000;McNeill and Perry, 2006;Wang et al, 2007;Amelio et al, 2008) have identified eNOS immunoreactivity in various fish tissues, including the vascular endothelium, when using heterologous mammalian eNOS antibodies (Olson and Donald, 2009;Imbrogno et al, 2014); and (3) Andreakis et al (2011) suggest that a neuronal NOS (nNOS) isoform with an 'endotheliallike' consensus may cover some functional features typical of the eNOS isoform. As has previously been reported for mammals (Taniguchi et al, 1999;Oliveira et al, 2009), we showed that NO is involved in A23187-mediated vasodilation of isolated trout coronary arterioles (Fig. 4A), and that this effect was completely dependent on the presence of an intact endothelium.…”
Section: Vasoactivity Of Recombinant Il-1β and The Effect Of Temperaturesupporting
confidence: 87%
“…It has long been known that intracellular Ca 2ϩ is an absolute requirement for eNOS activation (38). Furthermore, it is now widely accepted that when sustained NO production is triggered by a number of Ca 2ϩ -elevating agents such as the IP 3 generating agonist histamine, the SERCA inhibitor thapsigargin, or the Ca 2ϩ ionophore A-23187, the major source of this Ca 2ϩ is the influx of extracellular Ca 2ϩ via CCE (22,39,40). The localization of WTeNOS in plasma membrane caveolae, sites where CCE channels have also been proposed to reside (41), raised the tempting hypothesis that the decreased NO production by G2AeNOS upon stimulation of CCE was simply a result of the construct experiencing lower localized [Ca 2ϩ ] than the WTeNOS because of greater spatial separation from Ca 2ϩ influx channels.…”
Section: Discussionmentioning
confidence: 99%
“…BecauseA23187induceseNOSactivationandproducesendothelium-dependent vascular relaxation, Ca 2ϩ entry from the extracellular space into endothelial cells also plays a key role (19,59). Ca 2ϩ /calmodulin-dependent protein kinase kinase can activate and phosphorylate Akt (74).…”
Section: Discussionmentioning
confidence: 99%
“…A23187 induces eNOS activation and produces endothelium-dependent vascular relaxation (19,59). Thus, eNOS activity is largely regulated by Ca 2ϩ mobilization.…”
Section: Role Of Extracellular and Intracellular Ca 2ϩ In 17␤-e2-indumentioning
confidence: 99%